2003
DOI: 10.1093/intimm/dxg136
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric  2 microglobulin/CD3  polypeptides expressed in T cells convert MHC class I peptide ligands into T cell activation receptors: a potential tool for specific targeting of pathogenic CD8+ T cells

Abstract: CD8(+) T cells are key mediators of transplant rejection and graft-versus-host disease and contribute to the pathogenesis of autoimmune diseases. We tested whether TCR ligands can be converted into T cell activation receptors, redirecting genetically modified T cells at pathogenic CD8(+) T cells. For this purpose we exploited the ability of the non-polymorphic beta(2) microglobulin light chain to pair with all MHC class I heavy chains. In this report we describe the design and expression in a T cell hybridoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…We previously showed that expression of the peptide/b 2 m/anchor configuration resulted in exceptionally high occupancy of the restricting MHC-I product by the linked peptide. 9,40 To supplement the endogenous H-2K d in the polyclonal NOD CD8 T cells, we tested the addition of mRNA encoding H-2K d heavy chains. Figure 3A illustrates that the transfected polyclonal CD8 T cells have acquired the ability to kill the target CHIB2 cells and overexpression of H-2K d had no discernible effect on the killing activity.…”
Section: Functional Expression Of Peptide/b 2 M/cd3-z In Nod Cd8 T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that expression of the peptide/b 2 m/anchor configuration resulted in exceptionally high occupancy of the restricting MHC-I product by the linked peptide. 9,40 To supplement the endogenous H-2K d in the polyclonal NOD CD8 T cells, we tested the addition of mRNA encoding H-2K d heavy chains. Figure 3A illustrates that the transfected polyclonal CD8 T cells have acquired the ability to kill the target CHIB2 cells and overexpression of H-2K d had no discernible effect on the killing activity.…”
Section: Functional Expression Of Peptide/b 2 M/cd3-z In Nod Cd8 T Cellsmentioning
confidence: 99%
“…For cloning of the four constructs encoding peptide/human b 2 m/mouse CD3-z, we used essentially the same cloning strategy we described previously. 9 The gene segment encoding the full leader sequence of human The resulting XbaI/BamHI fragment and a BamHI/EcoRI fragment encoding the hb 2 m/CD3-z portion of the chimeric polypeptide 9 were inserted into pGEM4Z/A64.…”
Section: Assembly Of Genetic Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the pBJ1-Neo expression vector and the construction of plasmid 21-2, encoding chimeric human ␤ 2 m (h␤ 2 m)/CD3, have been described elsewhere (29).…”
Section: Vectors and Expression Plasmidsmentioning
confidence: 99%
“…The original design of membrane-anchored h␤ 2 m has already been delineated (29). Briefly, the carboxyl-terminal methionine residue of h␤ 2 m was genetically linked to a peptide bridge, comprising the 13 membrane-proximal amino acids of the extracellular portion of HLA-A2, LRWEPSSNPTIPI (single-letter code), which encompasses the proline-rich connecting peptide.…”
Section: Construction Of H␤ 2 M Harboring Two Different Membranal Ancmentioning
confidence: 99%